Initial luck, status-seeking and snowballs lead to corporate success and failure - Amihai Glazer; Vesa Kanniainen; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2004)
Corporate success stories often resemble a snowball. We show how initial luck in hiring talented people, the resulting technological advantage, superior corporate culture, and statusseeking by workers and by consumers can make small initial differences generate large differences over time.
Keywords: L13; L00; 330; industry equilibrium; initial luck; status effects; snowball; Unternehmensentwicklung; Prestige; Unternehmenskultur; Evolutionsökonomik; Innovationswettbewerb; Pfadabhängigkeit; Theorie